Biomedical Engineering Research in Chilean Universities - a Bibliometric Analysis - Villalobos-Cid, M (IEEE Computer Society, 2024)
Biomedical engineering (BME) combines engineering, biology, and medicine to develop innovative healthcare solutions. There is an increasing demand for BME professionals following technological and scientific advances. In Chile, only three universities offer undergraduate BME programs: Universidad de Valparaiso, Universidad de Concepcion, and Universidad de Santiago de Chile. Each institution has defined its curriculum, professional profile, and research focus based on its perspective of the country s needs. However, the scope of their research contribution has not been studied. In this work, we perform a comprehensive bibliometric analysis using data from the SCOPUS database to evaluate publications by researchers affiliated with Chilean undergraduate BME programs from 2000 to 2022. The objective is to identify the research areas of BME in Chile, understand the similarities and differences between universities, analyse their research areas, explore collaboration relationships, and characterise the discipline s evolution. The main contributions of this work are (1) a quantitative and qualitative analysis of BME research in Chile, (2) the identification of BME research areas and their development over time, (3) the creation of a dashboard-style web tool, and (4) proposing a robust methodology for bibliometric analysis applicable to BME literature in Chile and similar contexts. This work represents the first collaboration involving authors from all universities with undergraduate Chilean BME programs. © 2003-2012 IEEE.